Genetic Contributions to Loneliness and Their Relevance to the Evolutionary Theory of Loneliness. (May 2019) - Spithoven, A. W. M.; Cacioppo, S.; Goossens, L.; Cacioppo, J. T.
Loneliness is a negative and distressing emotional state that arises from a discrepancy between one's desired and achieved levels of social connectedness. The evolutionary theory of loneliness (ETL) posits that experiencing loneliness is an inherited adaptation that signals that salutary social relations are endangered or damaged and prompts people to reconnect to significant others. The basic tenets of the ETL has led researchers to examine the genetic underpinnings of loneliness. The current review provides an updated overview of genetic studies on loneliness and discusses the importance of genetic research for the ETL. The most recent studies suggest that the many genes that contribute to a small degree to differences in loneliness partially overlap with genes that contribute to neuroticism, but not with depression. In addition, the genetic studies discussed in this review show that genes are unlikely to have a direct effect on loneliness. Instead, environmental factors determine in a dynamic fashion how genes that contribute to loneliness are expressed. Future research on epigenetic processes, such as DNA methylation, can further elucidate the dynamic interplay between genes and the environment and how this interplay contributes to loneliness.